DETERMINAN RASIO KESEHATAN BANK, KEPEMILIKAN MANAJERIAL DAN UKURAN PERUSAHAAN PADA KEBIJAKAN DIVIDEN - Widhiastuti, Ni Luh Putu; Arista Pradnyani, I Gusti Agung (Universitas Boyolali, 2023)
Dividend policy is a decision regarding how much current profit will be paid as dividends in exchange for the investment made and how much will be retained for reinvestment in the company. This research aims to examine the influence of Capital Adequacy Ratio, loan to deposit ratio, return on assets, managerial ownership and company size on dividend policy. The population in this research is banking companies on the IDX for the 2018-2021 period, using a purposive sampling method to obtain a sample size of 8 banks. The data analysis technique used is multiple linear regression analysis. The research results state that the Capital Adequacy Ratio and company size have a positive effect on dividend policy. Meanwhile, loan to deposit ratio and managerial ownership have a negative effect on dividend policy. This is different from return on assets which has no influence on dividend policy. Future research can add other variables such as institutional ownership, company growth, leverage, or use moderating variables